2000
DOI: 10.1128/jcm.38.12.4439-4444.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Diagnostic Value of Taenia solium Low-Molecular-Weight Antigen Genes

Abstract: Neurocysticercosis (NCC) caused by infection with the larvae ofTaenia solium is an important cause of neurological disease worldwide. In order to establish an enzyme-linked immunosorbent assay (ELISA) for this infection using recombinant proteins, we carried out molecular cloning and identified four candidates as diagnostic antigens (designated Ag1, Ag1V1, Ag2, and Ag2V1). Except for Ag2V1, these clones could encode a 7-kDa polypeptide, and Ag2V1 could encode a 10-kDa polypeptide. All of the clones were very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 30 publications
2
28
0
4
Order By: Relevance
“…There was no indication of T. solium cysticercosis by serology using both native T. solium glycoprotein antigens 4 and recombinant antigen. 6 In Mongolia, pigs are kept indoors, and pig owners (non-nomadic or seminomadic people ‫ס‬ settlement) use simple latrine facilities with little free access to pigs. Nobody had a habit of consuming uncooked or undercooked pork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no indication of T. solium cysticercosis by serology using both native T. solium glycoprotein antigens 4 and recombinant antigen. 6 In Mongolia, pigs are kept indoors, and pig owners (non-nomadic or seminomadic people ‫ס‬ settlement) use simple latrine facilities with little free access to pigs. Nobody had a habit of consuming uncooked or undercooked pork.…”
Section: Discussionmentioning
confidence: 99%
“…For a total of 73 serum samples including 14 serum samples from people with histories of epileptic seizures, enzyme-linked immunosorbent assay (ELISA) and immunoblot were carried out using glycoproteins (GPs) purified by preparative isoelectric focusing from T. solium cyst fluids 4,5 and a recombinant chimeric T. solium antigen. 6 These assays were performed at Asahikawa Medical College, Japan, in 2004 and 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Research on antigenic features of surface proteins and cyst fluid and revised techniques of purification have resulted in the elaboration of improved serological applications. Nowadays, many scientists tend to use synthetic or recombinant proteins (7,38). It was shown that the specificity of these antigens is higher than that of native antigens; however, their sensitivity is predominantly lower (9).…”
Section: Diagnostics Of Porcine Cysticercosismentioning
confidence: 99%
“…Lentil-lectin affinity-purified GPs (177) have specific components with lower molecular weights, which are useful for detection of cysticercosis cases by WB, but also include nonspecific components of higher molecular weights which affect ELISA results (Figures 4 and 5). Recombinant antigens (186) show better specificity than the lentil-lectin affinity-purified GPs (177) and similar sensitivity to native antigens purified by isoelectrophoresis (183,184) and cation-exchange chromatography (187). There continues to be some debate on the best way to serologically detect cysticercosis.…”
Section: Miscellaneous Interestsmentioning
confidence: 99%
“…Western blot figures of cyst fluid of T. solium (a), lentillectin affinity-purified glycoproteins (GPs) (b) (177), two fractions of isoelectrofocusing purified GPs (c, d) (184) incubated with pooled pig sera confirmed infected with T. solium (panel a), with pooled NCC patients sera (panel b), and with a rabbit anti-A fraction GPs (c) by isoelectrofocusing (panel c)(184). Highly purified GPs isolated by isoelectrofocusing can be prepared by a very cheap cation-exchange chromatography(186).…”
mentioning
confidence: 99%